2018
DOI: 10.2298/vsp160203359b
|View full text |Cite
|
Sign up to set email alerts
|

Flexural strength and modulus of autopolimerized poly (methyl methacrylate) with nanosilica

Abstract: Background/Aim. Autopolymerized, or cold polymerized poly(methyl methacrylate) class of materials have a lower mechanical properties compared to hot polymerized poly(methyl methacrylate), due to a limited time of mixing before the polymerization process begins. The aim of this study was to test the effect of different relatively low nanosilica contents, in improving mechanical properties of the cold polymerized poly(methyl methacrylate). Methods. A commercially available autopolymerized poly(methyl methacrylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
(27 reference statements)
5
7
0
1
Order By: Relevance
“…In this work, the relatively low TiO2 nanoparticle content was applied. However, in some of our previous publications, which also studied the effect of relatively low SiO2 nanoparticle addition to PMMA [16,30] and flowable dental composite [35], some differences can be observed. Although mechanical properties increase was similar to this study, the maximum strengthening effect was observed at minimal tested nanoparticle loading of 0.05%.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In this work, the relatively low TiO2 nanoparticle content was applied. However, in some of our previous publications, which also studied the effect of relatively low SiO2 nanoparticle addition to PMMA [16,30] and flowable dental composite [35], some differences can be observed. Although mechanical properties increase was similar to this study, the maximum strengthening effect was observed at minimal tested nanoparticle loading of 0.05%.…”
Section: Resultsmentioning
confidence: 81%
“…In this paper, TiO2 nanoparticles were applied as a reinforcement for a cold cured poly/methylmethacrylate) denture relines resin, due to the inherent low mechanical properties of this type of polymer when it is cold cured. Namely, this material is used as a denture reline resin and for denture repair [16]. It is provided in the form of powder and liquid.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the existence of submicron and nanoparticle agglomerates. Agglomerates have a relatively low cohesive strength, due to the presence of relatively weak secondary bonds between particles, usually Van der Waals forces, hydrogen or capillary [33][34][35]. By mixing nano and submicron particles, their agglomerates suffer random collisions, as reported by Dongguang et al [36], causing a grinding effect, leading to the obtaining of smaller particles in the coating mixture, as revealed by Zeta sizer, Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Agglomerates have a relatively low cohesive strength, due to the presence of relatively weak secondary bonds between particles, usually Van der Waals forces, hydrogen or capillary [33][34][35]. By mixing nano and submicron particles, their agglomerates suffer random collisions, as reported by Frustum-type electrode tip results in a combined concentrated-spread arc, offering a combination of a higher penetration due to the flattened tip and the vaporization, dissociation, and decomposition of the oxides.…”
Section: Discussionmentioning
confidence: 99%
“…PMMA is used for denture reline resins as well, but they are cold, rather than hot polymerized. This material is used for providing a better retention of removable protheses in cases of alveolar resorption and denture reparation in case of crack or fracture 13 . The mechanical properties of cold polymerized denture reline resin is lower, as the result of a limited time for mixing the liquid and powder component, after which the radical polymerization commences.…”
Section: Introductionmentioning
confidence: 99%